RESHAPING PROJECT MANAGEMENT TOWARDS SUSTAINABLE DEVELOPMENT – METHODOLOGIES AND STANDARDS - Szajczyk, Marek; Krzepicka, Alicja (Management and Administration Journal, 2024)
In the contemporary business landscape, sustainability is emerging as a pivotal factor in project delivery, driven by stakeholder demands for ethicality, eco-consciousness, and economic efficiency throughout a project’s lifecycle. This study aims to identify and elucidate the norms and standards governing sustainable project management practices within project organizations. Our findings unveil that sustainable project management transcends mere reliance on indicators, embracing a comprehensive package of activities. This multifaceted approach adapts project management mechanisms to different sustainability dimensions. An important result of the analysis of research materials is also the list of seven identified areas of project management subject to transformation towards sustainability. This study probes the realm of sustainability within project management, unveiling its potential to curtail costs, amplify opportunities, and bolster organizational success. The conclusions of the paper emphasize that SPM (Sustainable Project Management) is not just a trendy word, but a necessity in the face of contemporary global challenges. Organizations must actively adapt to the sustainability paradigm and effective leaders are crucial to the success of sustainable projects.